Single variable calculus - Stewart, James (California Brooks/Cole Publishing Company, 1995)
Contents: limits and rates of change; derivatives; the mean value theorem and curve sketching; integrals; applications of integration; inverse functions; techniques of integration; further applications of integration,...
Includes index
Keywords: Cơ bản